Program Keselamatan dan Kesehatan Kerja Di Laboratorium Pendidikan - Dwi Cahyaningrum (Jurnal Pengelolaan Laboratorium Pendidikan, 2020)
The laboratory is a workplace that has potential hazards both physical, chemical, biological, and ergonomic hazards. Potential hazards in educational laboratories are considered lower than in industrial laboratories because they use relatively smaller amounts of material. This results in financial losses, injuries and damage to equipment and infrastructure. Some theories state that accidents that occur at work are the result of mistakes from humans and management. This paper discusses how to arrange and implement Occupational Safety and Health programs in educational laboratories so that potential hazards can be controlled and minimize workplace accidents.